Relative Handgrip Strength is Inversely Associated with Hypertension in Consideration of Visceral Adipose Dysfunction: A Nationwide Cross-Sectional Study in Korea - Park, Jae Ho; Lim, Nam-Kyoo; Park, Hyun-Young (Frontiers in Physiology, 2022)
This study investigated the associations of relative handgrip strength (rHGS) and hypertension. Individual differences in visceral adipose dysfunction (VAD) were evaluated to verify whether rHGS was associated with a reduction in the risk of hypertension, even in individuals with VAD. We included 77,991 participants (50,616 women) from nationwide cohorts in Korea. Participants were categorized into three groups based on sex-specific tertiles of rHGS (Low, Mid, and High). The visceral adiposity index (VAI) was used to evaluate VAD. The multiple logistic regression model was used to assess the risk of hypertension. High rHGS is associated with reduction of hypertension risk in 38% and 26% of men and women, respectively, although rHGS was significantly low in women compared to men. The benefit of rHGS was observed from middle-aged to older participants in both sexes. High rHGS is associated with risk reduction for hypertension in both VAD and non-VAD groups. In the VAD group, compared to Low rHGS, High rHGS was associated with 32% and 22% risk reductions in hypertension in men and women, respectively, and these associations remained significant even when classified according to age, such as in middle-aged and older subgroups. Therefore, the present study suggests that high levels of rHGS are significantly associated with a reduced risk of hypertension even in participants with VAD. Thus, maintaining a higher level of rHGS may be associated with protective benefits against hypertension.